Knowledge, Attitudes, and Practice Health Care Workers on Disposable Mask Waste Management in the Post-COVID-19 Pandemic - Wawan Ridwan; Endang Puji Astuti; Dede Anwar Musadad; Tities Puspita; Ristrini Ristrini; Gurendro Putro; Edy Suyanto; Siwi Pramatama (Jurnal Penelitian Pendidikan IPA, 2023)
Biomedical waste including disposable masks requires proper waste handling so it doesn’t pollute the environment and cause re-transmission of COVID-19 disease. The purpose of this study was to look at the relationship between the knowledge, attitudes and practices of the Public Health Centre in Pangandaran Regency. Methodology: Cross-sectional study approach to study assessed KAP. 91 participants were from 15 different public health centres in Pangandaran. Data analysis used chi-square statistical test. Presented with frequency distribution and the form of a tabulation. Result indicated knowledge of respondents was only 41.40% with high scores and practices with high scores were only 44.40% but attitudes towards disposable mask waste management with high scores reached 98.6%. There is a relationship between age and practice with a p-value of 0.009 and a relationship between knowledge and practice with a p-value below 0.05. Conclusion the participants had insufficient knowledge and practice scores but have good attitude scores. Our results conclude that the HCWs good attitude does not affect good practice but knowledge may lead to a proper practice. Findings of this study suggest that a regular training program for the HCWs on BMW specially on disposable mask management may lead to better practice